Lung function benefits of traditional Chinese medicine Qiju granules against fine particulate air pollution exposure: a randomized controlled trial - Chen, Rucheng; Zhang, Lu; Gu, Weijia; Li, Ran; Hong, Huihua; Zhou, Linshui; Zhang, Jinna; Wang, Yixuan; Ni, Ping; Xu, Shuqin; Wang, Zhen; Sun, Qinghua; et al. (Frontiers in Medicine, 2024)
Introduction Multiple targets are considered as the causes of ambient fine particulate matter [aerodynamic diameters of < 2.5 μm (PM2.5)] induced lung function injury. Qiju granules are derived from the traditional Chinese medicine (TCM) formula known as Qi-Ju-Di-Huang-Wan (Lycium, Chrysanthemum, and Rehmannia Formula, QJDHW), which has been traditionally used to treat symptoms such as cough with phlegm, dry mouth and throat, and liver heat. This treatment approach involves attenuating inflammation, oxidative stress, and fibrosis response. This study investigated the effects of Qiju granules on protecting lung function against PM2.5 exposure in a clinical trial. Methods A randomized, double-blinded, and placebo-controlled trial was performed among 47 healthy college students in Hangzhou, Zhejiang Province in China. The participants were randomly assigned to the Qiju granules group or the control group based on gender. Clinical follow-ups were conducted once every 2 weeks during a total of 4 weeks of intervention. Real-time monitoring of PM2.5 concentrations in the individually exposed participants was carried out. Data on individual characteristics, heart rate (HR), blood pressure (BP), and lung function at baseline and during the follow-ups were collected. The effects of PM2.5 exposure on lung function were assessed within each group using linear mixed-effect models. Results In total, 40 eligible participants completed the scheduled follow-ups. The average PM2.5 level was found to be 64.72 μg/m3 during the study period. A significant negative correlation of lung function with PM2.5 exposure concentrations was observed, and a 1-week lag effect was observed. Forced expiratory volume in one second (FEV1), peak expiratory flow (PEF), maximal mid-expiratory flow (MMEF), forced expiratory flow at 75% of forced vital capacity (FVC) (FEF75), forced expiratory flow at 50% of FVC (FEF50), and forced expiratory flow at 25% of FVC (FEF25) were significantly decreased due to PM2.5 exposure in the control group. Small airway function was impaired more seriously than large airway function when PM2.5 exposure concentrations were increased. In the Qiju granules group, the associations between lung function and PM2.5 exposure were much weaker, and no statistical significance was observed. Conclusion The results of the study showed that PM2.5 exposure was associated with reduced lung function. Qiju granules could potentially be effective in protecting lung functions from the adverse effects of PM2.5 exposure. Clinical Trial Registration identifier: ChiCTR1900021235.